The spectral profile of cortical activation during a visuospatial mental rotation task and its correlation with working memory - Anomal, Renata Figueiredo; Brandão, Daniel Soares; Souza, Rafaela Faustino Lacerda de; Oliveira, Sóstenes Silva de; Porto, Silvia Beltrame; Hazin Pires, Izabel Augusta; Pereira, Antonio (Frontiers in Neuroscience, 2023)
The search for a cortical signature of intelligent behavior has been a longtime motivation in Neuroscience. One noticeable characteristic of intelligence is its association with visuospatial skills. This has led to a steady focus on the functional and structural characteristics of the frontoparietal network (FPN) of areas involved with higher cognition and spatial behavior in humans, including the question of whether intelligence is correlated with larger or smaller activity in this important cortical circuit. This question has broad significance, including speculations about the evolution of human cognition. One way to indirectly measure cortical activity with millisecond precision is to evaluate the event-related spectral perturbation (ERSP) of alpha power (alpha ERSP) during cognitive tasks. Mental rotation, or the ability to transform a mental representation of an object to accurately predict how the object would look from a different angle, is an important feature of everyday activities and has been shown in previous work by our group to be positively correlated with intelligence. In the present work, we evaluate whether alpha ERSP recorded over the parietal, frontal, temporal, and occipital regions of adolescents performing easy and difficult trials of the Shepard-Metzler's mental rotation task, correlates or are predicted by intelligence measures of the Weschler’s intelligence scale. We used a database obtained from a previous study of intellectually gifted (N = 15) and average intelligence (N = 15) adolescents. Our findings suggest that in challenging task conditions, there is a notable difference in the prominence of alpha event-related spectral perturbation (ERSP) activity between various cortical regions. Specifically, we found that alpha ERSP in the parietal region was less prominent relative to those in the frontal, temporal and occipital regions. Working memory scores predict alpha ERSP values in the frontal and parietal regions. In the frontal cortex, alpha ERSP of difficult trials was negatively correlated with working memory scores. Thus, our results suggest that even though the FPN is task-relevant during mental rotation tasks, only in the frontal region alpha ERSP is correlated with working memory score in mental rotation tasks.